Postmodern advertising: a longitudinal study of super bowl commercials - Zotos, Yorgos; Hatzithomas, Leonidas; Outra, Evvangelia (My University, 2010)
The present study examines the impact of postmodernism on advertising content, through a longitudinal analysis of 1.516 Super Bowl commercials that shown during the last 40 years (1969-2009). Moreover, for the Super Bowl commercials screened during the last decade (2000), the attitude towards the ad was measured, using USA Today Ad Meter scores as a dependent variable. The findings reveal that the use of “postmodern advertising devices” (such as surreal visuals, symbolic associations and humorous juxtapositions) has been increased during the last four decades. On the contrary, “modern advertising approaches” (such as realistic visuals, the use of experts and high levels of information content) have been reduced. Besides, it seems that “postmodern advertising approaches” lead to significantly more positive attitudes toward the ad, during the last decade.
Keywords: Postmodernism; Super Bowl Commercials; Attitude toward the Ad; Advertising; Promotion and marketing communications